Bank capital, borrower power, and loan rates - Santos, João A. C. (2019)
We examine how bank capital and borrower bargaining power affect loan spreads. Consistent with previous studies, higher bank capital has a negative impact on loan rates, but borrower cash flow has a significant effect on this impact: Compared with high-capital banks, low-capital banks charge more for borrowers with low cash flow, but offer greater marginal discounts as these borrowers' cash flow rises. These effects are largely focused on more bank-dependent borrowers. We find some evidence that low-capital banks charge a higher premium for bank-dependent borrowers' systematic risk, but not for their total equity risk or default risk. Received January 27, 2015; editorial decision July 7, 2018 by Editor Philip Strahan. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.